An Exploratory Study on Virtual Reality and Related Technologies in Terminal LIS Degree Programs in the United States and South Korea - Hollister, Jonathan Michael; Lee, Jisue (International Journal of Knowledge Content Development & Technology, 2022)
With growing public, educational, corporate, and governmental interests in the “Metaverse” and 4th Industrial Revolution, virtual, augmented, mixed, or extended reality technologies have seen renewed interest and expanded adoption across contexts. While libraries and librarians have long provided their communities access to information, media, and technology, and are not strangers to virtual worlds, there is little work on whether LIS programs are preparing pre-service librarians to be knowledgeable of VR and related technologies and their applications in libraries and other information organizations. As such, this study employs a selected literature review on how libraries provide and use virtual reality and related technologies in their collections, programs, and services as well as a summative content analysis exploring the inclusion and use of virtual reality and related technologies in the curricula of terminal LIS degree programs in the United States and South Korea. The literature review identified three key, interconnected themes: stakeholder partnerships, content development, and inclusion and accessibility. Findings from the summative content analysis suggest that the level of inclusion of VR and related technologies in terminal LIS programs is low in both the United States and South Korea. Of the few existing courses covering XR technologies, it appears that most cover content development, while fewer address issues related to stakeholder partnerships, and inclusion and accessibility. Recommendations for LIS educators interested in developing courses or training about VR and related technologies in libraries are discussed.